EKRANISASI NOVEL KE FILM SURAT KECIL UNTUK TUHAN - Prastika Aderia; Hasanuddin WS Hasanuddin WS; Zulfadhli Zulfadhli (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this article (a) to describe story of episode novel Surat Kecil untuk Tuhan created by Agnes Davonar, (b) to describe story of episode film Surat Kecil untuk Tuhan director by Harris Nizam, (c) to describe similar and different story of episode novel with film Surat Kecil untuk Tuhan. The Data of this study were story of episode novel Surat Kecil untuk Tuhan created by Agnes Davonar and film Surat Kecil untuk Tuhan director by Harris Nizam. Analyzed technique do with ekranisasi theory. The findings of the study showed that the decrease story of episode novel Surat Kecil untuk Tuhan created by Agnes Davonar in film Surat Kecil untuk Tuhan director by Harris Nizam become to 69 story of episode. Increase story of episode in film Surat Kecil untuk Tuhan director by Harris Nizam become to 27 story of episode. The same variation changes event, figure and background story of episode in novel Surat Kecil untuk Tuhan created by Agnes Davonar and film Surat Kecil untuk Tuhan director by Harris Nizam become to 32 story of episode. Kata kunci : novel, film, ekranisasi, episode cerita